Analysis of the Popularity of Integrated Islamic Elementary Schools (SDIT) in Jambi Province: A Study of Growth and Parental Preference Factors (2019-2024) - Fadlilah; Muhaiminah Jalal; Kiki Fatmawati (Global Action and Education for Society, 2025)
This research analyzes the popularity of Integrated Islamic Primary Schools (SDIT) in Jambi Province through a study of growth and parent preference factors during the 2019-2024 period. Using a qualitative approach, the research was conducted at four SDITs in Jambi Province, namely SDIT Al Muthmainnah Jambi City, SDIT Nurul Hikmah East Tanjung Jabung, SDIT Diniyah Al Azhar Tebo, and SDIT Al Azhar 57. Data were collected through observation, structured interviews, and documentation with research subjects including principals, teachers, parents, and students. The data were analyzed using a qualitative descriptive method referring to the research design of Miless et al. The results showed a significant increase in the number of SDITs in Jambi Province by 85.7% from 49 schools in 2019 to 91 schools in 2024. The high public interest is reflected in the large number of study groups and students in each sample school, with an average of 15-29 students per rombel. Factors that influence the popularity of SDIT include the quality of character education, the balance of general education with Islamic values, excellent programs, the development of student independence, and full day school services that accommodate the needs of working parents. This research contributes to the understanding of the phenomenon of SDIT growth and parents' preferences in choosing integrated Islamic education institutions.